Photo/redox-responsive 2D-Supramolecular assembly involving Cucurbit[8]uril and a star-shaped porphyrin tecton. (1st September 2019) - Chowdhury, Shagor; Nassar, Youssef; Guy, Laure; Frath, Denis; Chevallier, Floris; Dumont, Elise; Ramos, Ana Paula; Demets, Grégoire Jean-François; Bucher, Christophe
Abstrac: The present paper reports on the formation and on the electrochemical/spectroscopic characterization of inclusion complexes formed in aqueous media between cucurbit[7 or 8]urils cavitands (CB[7], CB[8 ]) and a rigid four-pointed star-shaped viologen-appended porphyrin tecton. The formation of discrete 4:1 pseudo-rotaxane-like caviplexes, involving threading of CB[n] rings on the rigid viologen-based star's branches has been demonstrated by nuclear magnetic resonance and mass spectrometry measurements. Then, the photo- and redox-triggered formation of 2D supramolecular assemblies involving CB[8]s and the four electron reduced tectons as key building elements, has been established on the ground of in-depth electrochemical and spectroscopic analyses supported by quantum calculations. The CB[8]-promoted intermolecular π-dimerization of the viologen cation radicals introduced at the meso positions of the porphyrin plateform has been brought to light through the diagnostic signatures of the 1:2 host-guest ternary caviplexes formed between viologen and CB[8] and by spectroscopic data collected after electrochemical, chemical or photochemical reduction of the viologen-based tectons. The CB[8] hosts not only proved useful to promote the redox-triggered formation of supramolecular assemblies, it was also found to prevent the chemical reduction of the porphyrin ring in aqueous media and its subsequent conversion into phlorin products.